Kekuasaan Kehakiman dalam Islam dan Aplikasinya di Indonesia - Lomba Sultan (Al-Ulum, 2013)
Islamic constitution context recognizes three agencies of state power, namely: the executive power (sulthah tanfiziyah), the legislative power (sulthah tasyri `iyah), and the judicial power (sulthah qadha` iyah). During the Rasulullah periods, all three agencies concetrated on one region of power; but during the Khalifah Umar Bin Khattab, the judicial power begin separate caused the Islamic region extends out Arabiah peninsula. Furthermore during the Umar bin Abdul Aziz regime, judicial power especially al-hisbah and al-mazalim can really be enforced in accordance with good public sense of justice. It happened because the law enforcement wer implemented without any selective with each other. Therefore, if the two kind of agencies can also be applied in Indonesia, besides the existing judicial institutions under the Supreme Court that the General Court, the Religious Courts, Military Justice, and State Administrative Court, then the problem of law enforcement and justice can be resolved according to expectations of society.